Incisional Hernia Cases and Repair in last five years at Dhaka National Medical College Hospital (DNMCH) - Jahan, Shamima; Rahman, Md Motiar (Journal of Dhaka National Medical College & Hospital, 2016)
Background: An incisional hernia is a hernia that occurs through a previously made incision in the abdominal wall1. A good number of patient presents with Incisional Hernia following various surgery at various stage. Though safe, surgical approach is widely adopted, still incisional hernia continues. Objective: Evaluation of patients presenting with incisional hernia and also to observe the hazards of hernioplasty. Materials and Methods: It is a retrospective study carried out in Surgery dept. at unit-I, DNMCH from June 2011 to May 2016 among the admitted patients, who underwent surgical repair in this hospital. Results: This study includes 34 (n-34) women between 26 to 65 yrs (mean age-37.32) yrs of age. Most of them are from middle & lower middle class family. Among the 34 women, 31 (91.18%) previously had various lower abdominal surgery, 1 person have post traumatic repair surgery, 2 (5.88%) had hernia from umbilical port following laparoscopic surgery. 28 (82.35%) women were obese. 4 (11.77%) patients were diabetic, 2 patients have chronic bronchial Asthma, 6 (17.7%) patients gave history of wound infection following primary surgery. After proper evaluation, hernioplasty with Prolene Mesh was done. Among the 28 obese person, 20 (58.8%) patient develop variable degree of seroma. 19 patient recovered subsequently but persists in one patient where seroma persisted for up to 6-wks. She was advised for readmission & removal of mesh under anaesthesia. Average hospital stay is 6 days but follow-up continued up to 8 wks. Discussion: Obesity is the commonest reason for incisional hernia. Diabetes mellitus & Bronchial Asthma must be controlled before elective surgery. Regarding post operative seroma, it is a recognized complication of synthetic mesh induced hernioplasty.3 Conclusion: Social awareness must be created against obesity. J. Dhaka National Med. Coll. Hos. 2016; 22 (01): 27-28